Improving Elementary School Students' Understanding of the Concept through Meaningful Learning in David Ausbel's Perspective - Andi Nurhasanah; Sri Ramadhanti; Sapriya Utami; Fia Alifah Putri (Universitas Pahlawan Tuanku Tambusai, 2022)
Meaningful learning proposed by David Ausubel is a process that connects new information with relevant concepts that exist in the cognitive structure of students. The purpose of this study was to determine the level of understanding of the concept of elementary school students through meaningful learning (meaningful learning) David Ausubel. The method used in this research is descriptive qualitative research method. The results show that the use of Ausubel's meaningful learning theory in learning is the main attraction for students in carrying out learning activities, because the use of this strategy is a new way for them to acquire and develop their knowledge, in which students' cognitive abilities increase. In the learning process with Ausubel's meaningful learning theory, there are factors that support and hinder the learning process. Supporting factors such as teacher pedagogic competence and adequate infrastructure. While the inhibiting factors, namely the differences in the abilities and characteristics of students who are different and the spirit of learning is different.